Factors influencing the literacy of zakat on income in Lembaga Zakat Selangor, Selangor, 2008 / Nur Hazirah Amat Zakaria - Amat Zakaria, Nur Hazirah (Faculty of Business and Management, 2005)
Lembaga Zakat Selangor(LZS) were establishment as one of the non-profit entity to administer the collection of all kind of zakat in Selangor such as zakat on income, zakat on business, zakat on saving, zakat on gold and silver, zakat on stocks/shares, zakat on employees provident fund (EPF), zakat on crops and zakat on livestock. All these kind of zakat are compulsory to eligible Muslims who fulfill the rules that make them compulsory to pay zakat. The largest contribution of zakat payment is zakat on income but there has still many Muslims not pay zakat where only two hundred thousands from two million Muslims pay the zakat on income. Therefore, the main objective of this research is to study on "Factors Influencing the Literacy of Zakat on Income in Lembaga Zakat Selangor, Selangor, 2008". This study examined some relevant factors that include are promotion activities, attitudes towards zakat on income, religiousness, education level and demographic factors towards literacy of zakat on income. For the purpose of this study, 100 questionnaires were distributed to Muslims who live in Selangor by using Non-probability Sampling Technique. Questionnaires were distributed as the survey instrument as the source of primary data, other reliable resources would serve as secondary data. This study finding indicates that all factors such as promotion activities, attitudes towards zakat on income, religiousness and education level have significant relationship towards literacy of zakat on income except demographic factors.